PENGARUH NANOEMULGEL JINTAN HITAM (Nigella sativa) TERHADAP JUMLAH FIBROBLAS DALAM PENYEMBUHAN LUKA PASCA PENCABUTAN GIGI PADA TIKUS - Karini, Nagita Dari (Faculty of Dentistry, Universitas Islam Sultan Agung, 2024)
Background: Tooth extraction is said to be successful when accompanied by a good wound healing process. An innovation for the treatment of post-tooth extraction wounds is necessary with the use of herbal plants. Black cumin (Nigella sativa) has active ingredients that function as anti-inflammatories, one of which can increase fibroblast levels. The formulation used is nanoemulgel because it has the advantages of stability and good adhesion, providing good delivery of drugs and active substances. Purpose: To see the effect of black cumin extract nanoemulgel (Nigella sativa) on the number of fibroblasts in the wound healing process after tooth extraction in rats. Method: this study was conducted with a post-test only control group design design with a total sample of 22 samples divided into 4 groups with each group totaling 5 samples and 2 samples as a drop out of the black cumin nanoemulgel treatment group, 4 groups consisting of the black cumin nanoemulgel group (Nigella sativa ) with a concentration of 10% and 15%, gengigel gel and, aquades. The application of black cumin nanoemulgel preparations with a concentration of 10% and 15%, gengigel gel, and aquades is carried out as much as 3x a day for 5 days. Tissue retrieval in experimental animals was carried out by cutting the lower jaw of the rat then ahistological preparation was made from a paraffin block. The calculation was carried out using hematoxylin eosin (HE) staining with a magnification of 400x and was carried out in the apical 1/3 area of 3 field of view with a V-pattern of the letter V, namely on the left, middle and right. The test used is the One Way Anova test and Post Hoc LSD test. Research results: The number of fibroblasts in the black cumin nanoemulgel treatment group with a concentration of 15% is more than that of the black cumin nanoemulgel treatment group with a concentration of 10% and aqueous. The results of the One Way Anova test showed a value of p